1994
DOI: 10.21236/ada290021
|View full text |Cite
|
Sign up to set email alerts
|

Scheduler-Conscious Synchronization.

Abstract: Efficient synchronization is important for achieving good performance in parallel programs, especially on large-scale multiprocessors. Most synchronization algorithms have been designed to run on a dedicated machine, with one application process per processor, and can suffer serious performance degradation in the presence of multiprogramming. Problems arise when running processes block or, worse, busy-wait for action on the part of a process that the scheduler has chosen not to run.In this paper we describe an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 16 publications
(28 reference statements)
0
6
0
1
Order By: Relevance
“…Imagine the code running on a two-processors machine: after main completes its execution, each philosopher embarks on a busy-waiting loop, only that two of them will be running in processors, while the third is (and will indefinitely remain) in the run-pool. Situations of deadlocks comprising suspended code are known to be difficult to deal with [13]. Our notion of deadlocked state takes into account running and suspended threads.…”
Section: Introductionmentioning
confidence: 99%
“…Imagine the code running on a two-processors machine: after main completes its execution, each philosopher embarks on a busy-waiting loop, only that two of them will be running in processors, while the third is (and will indefinitely remain) in the run-pool. Situations of deadlocks comprising suspended code are known to be difficult to deal with [13]. Our notion of deadlocked state takes into account running and suspended threads.…”
Section: Introductionmentioning
confidence: 99%
“…21 Competitive succession is also called barging, as arriving threads can barge in front of other waiting threads, allowing unbounded bypass and grossly unfair admission. 22 Kontothanassis et al [50] and He et al [42] suggested ways to mitigate this problem for MCS locks. 23 Unpark itself incurs a cost of more than 9000 cycles to the caller on our SPARC T5 system.…”
Section: Reentrantlockmentioning
confidence: 99%
“…Preemption, blocking, page faulting, and many other hazards that can befall the lock holder can be addressed through the use of scheduler-conscious synchronization [8]. Some form of scheduler-conscious synchronization is supported by each of the mainstream operating systems, including Linux, due to the fact that it is relied on by certain database kernels.…”
Section: Improving Lockingmentioning
confidence: 99%